Sphincter-Preserving Fistulectomy Is an Effective Minimally Invasive Technique for Complex Anal Fistulas - Hong, Yinwen; Xu, Zhizhong; Gao, Ying; Sun, Mingming; Chen, Yinghui; Wen, Ke; Wang, Xiaopeng; Sun, Xueliang (Frontiers in Surgery, 2022)
Background: The optimal treatment of complex anal fistulas remains unclear, though many different sphincter-preserving procedures have been described. A minimally invasive technique with a better outcome is desired. The purpose of this study was to present a new technique - sphincter-preserving fistulectomy (SPF) and its clinical outcomes. Materials and Methods: A retrospective study was performed to compare the efficacy and outcomes of SPF with ligation of the intersphincteric fistula tract (LIFT) in the management of complex anal fistulas in regards to postoperative pain, complications, wound healing time, recurrence, overall success rate, fecal continence function, and quality of life. Continence function was evaluated using the Wexner incontinence scale and anal manometry. The fecal incontinence quality of life (FIQL) scale was used to assess patients’ quality of life. Results: From June 2020 to July 2021, 41 patients with 43 SPF procedures and 35 patients with 35 LIFT procedures were included. Postoperative pain was comparable between two groups. The morbidity rate and the mean wound healing time in SPF group were lower than those in LIFT group (2.3% vs. 48.6%, P < 0.001; 1.4±0.3 vs. 1.7±0.4 months, P = 0.001). At a mean follow-up duration of 8.4±3.5 months in SPF group and 7.7±4.3 months in LIFT group, SPF achieved a better overall success rate than LIFT (97.7% vs. 77.1%, P = 0.009). Three patients in SPF group and 4 patients in LIFT group who all underwent a simultaneous fistulotomy procedure complained new incontinence of flatus. There was no statistical difference between two groups in regards to the Wexner scores (P = 0.790), the maximum resting anal canal pressure (P = 0.641), the maximum squeeze pressure (P = 0.289), and the FIQL scores including lifestyle (P = 0.188), coping (P = 0.188), depression (P = 0.850) and embarrassment (P = 0.910). Conclusions: SPF is a novel, safe, and effective minimally invasive technique for the management of complex anal fistulas, with a promising success rate and negligible impairment on continence. Future prospective studies are needed to evaluate the long-term outcomes of SPF.